2021
DOI: 10.1039/d1sm00441g
|View full text |Cite
|
Sign up to set email alerts
|

Degradable and processable polymer monoliths with open-pore porosity for selective CO2 and iodine adsorption

Abstract: Task-specific design of biodegradable and processable porous polymers is one of the primary requisite for their efficient day-to-day use to minimize polymer waste. Herein, a surfactant (or additive) free method...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…25,26 In this context, it was observed that functional amines when embedded within a polarizable network such as polyaromatic amines and polyaminoamides show excellent iodine adsorption ability. [27][28][29][30] However, most of the reported materials demonstrate iodine adsorption ability only in the vapor phase and organic solvents. [31][32][33][34][35][36][37] Materials which show signicant iodine adsorption ability in water, are much less reported.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In this context, it was observed that functional amines when embedded within a polarizable network such as polyaromatic amines and polyaminoamides show excellent iodine adsorption ability. [27][28][29][30] However, most of the reported materials demonstrate iodine adsorption ability only in the vapor phase and organic solvents. [31][32][33][34][35][36][37] Materials which show signicant iodine adsorption ability in water, are much less reported.…”
Section: Introductionmentioning
confidence: 99%
“…In other work, porous polyelectrolyte polymers were synthesized for iodine and CO 2 adsorption using colloidal templating involving the sol–gel strategy. [ 73 ] Tris(2‐aminoethylamine) monomer was reacted with N,N ′‐methylene (bis)acrylamide to form colloidal NPs, which on long‐duration (48 h) stirring form a cross‐linked gel. The freeze‐dried polymer can be further used in powder as an adsorbent material.…”
Section: Synthesis Methods Of Porous Materialsmentioning
confidence: 99%
“…In the past few decades, polyamine-based microgels have attracted significant attention due to their application toward the removal of anionic dyes and heavy metal ions. The polyamine microgel has a positive charged surface because of protonated amine functionality, which results in electrostatic interaction with negatively charged pollutants, facilitating their elimination. , To explain the adsorption of heavy metal ions and anionic dyes, a plausible mechanism has been proposed where efficient adsorption of toxic metal ions is caused due to the chelation of metal ions with the amine-based chelating groups in addition to various supramolecular interactions (electrostatic interaction, H-bonding interaction, and π–π interaction). …”
Section: Applications Toward Environmental Remediationmentioning
confidence: 99%